Professional Ethics of Software Engineers: An Ethical Framework. - Lurie, Yotam; Mark, Shlomo (Science & Engineering Ethics, 2016)
The purpose of this article is to propose an ethical framework for software engineers that connects software developers' ethical responsibilities directly to their professional standards. The implementation of such an ethical framework can overcome the traditional dichotomy between professional skills and ethical skills, which plagues the engineering professions, by proposing an approach to the fundamental tasks of the practitioner, i.e., software development, in which the professional standards are intrinsically connected to the ethical responsibilities. In so doing, the ethical framework improves the practitioner's professionalism and ethics. We call this approach Ethical-Driven Software Development (EDSD), as an approach to software development. EDSD manifests the advantages of an ethical framework as an alternative to the all too familiar approach in professional ethics that advocates 'stand-alone codes of ethics'. We believe that one outcome of this synergy between professional and ethical skills is simply better engineers. Moreover, since there are often different software solutions, which the engineer can provide to an issue at stake, the ethical framework provides a guiding principle, within the process of software development, that helps the engineer evaluate the advantages and disadvantages of different software solutions. It does not and cannot affect the end-product in and of-itself. However, it can and should, make the software engineer more conscious and aware of the ethical ramifications of certain engineering decisions within the process.